Margaret Thatcher's Vision on the Russian Factor in the International Relations System (Late Twentieth – Early Twenty-First Century) - Cherevko, O. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2021)
The article analyzes the memoirs and scientific legacy of the Prime Minister
of the United Kingdom during 1979–1990 Margaret Thatcher on the role of the
USSR and Russia in the international relations system of the last third of the
20th – early 21st century. The evolution of Soviet/Russian-British relations in the
active phase of the Cold War and its gradual extinction is studied: from the categorical
rejection of the Soviet political regime at a time of stagnation to the establishment
of active dialogue during the period of rebuilding and Gorbachev’s
“new political thinking”. The paper focuses on the predictions of a respected
British politician regarding Russia’s role in the future of Europe and the world.
The role of the nuclear factor in the implementation of Soviet-British relations is
analyzed. The process of implementation of the “German question” through the
prism of these relations is considered. The role of the United States as an important
factor influencing the course of the Soviet/Russian-British dialogue is defined,
in particular in the context of NATO’s role, operation “Desert Storm”. The
paper describes the main problems of Europe and the world, exacerbated during
the collapse of the Soviet Union. Particular attention is paid to the consideration
of interpersonal relations between Margaret Thatcher and Mikhail Gorbachev
and the characteristics of his successors as leader of the state: Boris Yeltsin and
Vladimir Putin. У статті проаналізовано мемуарну та наукову спадщину прем’єр-міністра Великої Британії (1979‒1990 рр.) Маргарет Тетчер щодо ролі
СРСР та Росії у системі міжнародних відносин останньої третини ХХ ‒
початку ХХІ століття. Досліджено еволюцію радянсько/російсько-британських відносин в умовах активної фази «холодної війни» та поступового її
згасання: від категоричного несприйняття радянського політичного режиму стадії застою до налагодження активного діалогу в період перебудови та «нового політичного мислення» М. Горбачова, процес кризи та
розпаду СРСР, прогнози авторитетного політика щодо ролі Росії у майбутньому Європи та світу. Проаналізовано роль ядерного чинника у процесі здійснення радянсько-британських відносин. Розглянуто процес реалізації
«німецького питання» через призму цих відносин. Визначено роль США з
огляду на їхній вплив на перебіг радянсько/російсько-британського діалогу,
зокрема в контексті ролі НАТО, операції «Буря в пустелі». Окреслено основні проблеми Європи та світу, що загострилися у процесі розпаду СРСР. Окрему увагу приділено розгляду міжособистісних стосунків М. Тетчер і
М. Горбачова та характеристикам його наступників на посаді лідера держави ‒ Б. Єльцина та В. Путіна.